2011
DOI: 10.1002/bem.20693
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome expression analysis in primary human keratinocyte cell cultures exposed to 60 GHz radiation

Abstract: The main purpose of this study is to investigate potential responses of skin cells to millimeter wave (MMW) radiation increasingly used in the wireless technologies. Primary human skin cells were exposed for 1, 6, or 24 h to 60.4 GHz with an average incident power density of 1.8 mW/cm(2) and an average specific absorption rate of 42.4 W/kg. A large-scale analysis was performed to determine whether these exposures could affect the gene expression. Gene expression microarrays containing over 41,000 unique human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Nicolaz et al [22] described that exposure to 60.4 GHz radiation at a power density of 0.14 mW/cm 2 did not cause endoplasmic reticulum stress in human glial cells. Le Dréan’s group has also published studies on the effects of 60.4 GHz radiation [23,24,25]. Le Quément et al [23,24] showed no significant differences in gene expression following exposure to millimeter-wavelength radiation: although after 6 h exposure at 20 mW/cm 2 real-time PCR analysis showed that some gene expression levels were affected, and this effect was linked to the increased temperature caused by exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicolaz et al [22] described that exposure to 60.4 GHz radiation at a power density of 0.14 mW/cm 2 did not cause endoplasmic reticulum stress in human glial cells. Le Dréan’s group has also published studies on the effects of 60.4 GHz radiation [23,24,25]. Le Quément et al [23,24] showed no significant differences in gene expression following exposure to millimeter-wavelength radiation: although after 6 h exposure at 20 mW/cm 2 real-time PCR analysis showed that some gene expression levels were affected, and this effect was linked to the increased temperature caused by exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Le Dréan’s group has also published studies on the effects of 60.4 GHz radiation [23,24,25]. Le Quément et al [23,24] showed no significant differences in gene expression following exposure to millimeter-wavelength radiation: although after 6 h exposure at 20 mW/cm 2 real-time PCR analysis showed that some gene expression levels were affected, and this effect was linked to the increased temperature caused by exposure. Haas et al [25] also indicated that a slight increase in protein expression observed following exposure to 60.4 GHz for 24 h was related to heating, and that there were no differences in the protein expression of neuronal marker β-tubulin or in the internal expression of control β-tubulin, consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the size and the density of networks are growing rapidly, there is a need to keep the levels of radiation below these thresholds at the level of design and control of the networks. There is an ongoing research on the medical aspect of radio frequency radiation impact and the results are inconclusive and rather controversial [2], [3], [4], but that is out of the scope of this paper. We are interested in the algorithmic aspects of the problem instead, in particular, in the problem of finding low radiation paths between specified points in the network enhanced area.…”
Section: Introductionmentioning
confidence: 88%
“…Logani et al [92] concluded that mmWaves are not genotoxic, which is perhaps not surprising due to the nonionizing nature of the mmWave band. Quément et al [93] reported a thorough study showing that mmWave exposure at 60.4 GHz with an average incident power of 1.8 mW/cm 2 and an average SAR of 42.4 W/kg did not have any dramatic impact on primary human keratinocyte cells. Zhadobov et al [94] presented a study on the influence of low-PD (5.4-μW/cm 2 or 0.54-mW/cm 2 ) mmWave radiation at 60 GHz of stress-sensitive gene expression of molecular chaperones in a human brain cell line.…”
Section: Reported Effects At Cellular and Molecular Levelsmentioning
confidence: 99%